Cytological and Microbial Investigation of Cervicitisby Endocervical Cytobrushe Smear in Some Iraqi Women Patients - Eman Natiq Naji (Journal of Global Pharma Technology, 2018)
This study is interested with occurrence and evaluationof cervicitis by endocervical cytobrushe smearin a sample of Iraqi women (87) who attending to the obstetrics and gynaecology outpatient clinic in AL-Numan hospital complaining from certain symptoms for a period of 6 months. Samples were obtained from cervical and endocervicl area,divided into 2 parts; cytological and microbiological tests have been curried out . Smears were prepared in order to detect inflammation and non inflammation changes in endocervical cells .Microbiological investigation has been performed to identified suspected pathogens; bacterial isolates; Candidaspp.and Trichomonas vaginalis. Results of cytological aspectwere shown as Increasing in number of lymphocytes and neutrophils indicating that there is an acute inflammation besides of clusters of squamous cells in many area, squamous intraepithelial cells with nuclei were increased in size and shape in addition to containing hyperchromatic , membrane irregularities and thickness have appeared. On the other hand, aggregation of inflammatory cells with numerous squamous cells has been noticed.Microbiological results were represented by detection of several aerobic and aeaerobic bacteria accompanied with the infection in addition to Candidaalbicance and Candidaglabrata.A total of79 samples have been tested; 44 (55.7%) were positivefor culturedistributed between acute29 (36.7%); and chronic;15 (18.98%).Thehighest isolation percentages were for C.albicance (15.9%), followed by different bacterial spescies ; Gardnerella vaginalis (13.6%), Staphylococcus aureus(11.3) in acute cervicitis cases,the lowest was for Lactobacillus acidophilus (0%) while in chronic cervicitis ,the highest percentage was (3.6%) for each of S.aureus ,G.vaginalis,L.acidophilus and C.albicance.Keywords: Cervicitis, Endocervical cells, Aerobic & anaerobic bacteria.